Nicotinic modulation of glutamate receptor function at nerve terminal level: a fine-tuning of synaptic signals - Marchi, Mario; Grilli, Massimo; Pittaluga, Anna M. (Frontiers in Pharmacology, 2015)
This review focuses on a specific interaction occurring between the nicotinic cholinergic receptors (nAChRs) and the glutamatergic receptors (GluRs) at the nerve endings level. We have employed synaptosomes in superfusion and supplemented and integrated our findings with data obtained using techniques from molecular biology and immuno-cytochemistry, and the assessment of receptor trafficking. In particular, we characterize the following: 1) the direct and unequivocal localization of native α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) and N-methyl-D-aspartate (NMDA) glutamatergic receptors on specific nerve terminals, 2) their pharmacological characterization and functional co-localization with nAChRs on the same nerve endings, and 3) the existence of synergistic or antagonistic interactions among them. Indeed, in the rat nucleus accumbens (NAc), the function of some AMPA and NMDA receptors present on the dopaminergic and glutamatergic nerve terminals can be negatively or positively regulated in response to a brief activation of nAChRs. This effect occurs rapidly and involves the trafficking of AMPA and NMDA receptors. The event takes place also at very low concentrations of nicotine and involves the activation of several nAChRs subtypes. This dynamic control by cholinergic nicotinic system of glutamatergic NMDA and AMPA receptors might therefore represent an important neuronal presynaptic adaptation associated with nicotine administration. The understanding of the role of these nicotine-induced functional changes might open new and interesting perspectives both in terms of explaining the mechanisms that underlie some of the effects of nicotine addiction and in the development of new drugs for smoking cessation.